(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
This study was conducted to identify seasonal infestations of parasites in Channa punctatus of Dinajpur, Bangladesh. Sampling was carried out frequently over a year in selected cultural and natural sources. A total of 120 fish was examined among them 32 fishes were infested and collected parasites were 72. Two parasites were recorded, Genarchopsisdasus and Camallanusanabantis. The prevalence was found 26.67 % and mean intensity 2.41. The maximum prevalence was found in August (50 %) and the lowest in December, January, February (10 %). The maximum mean intensity was January (8) and the lowest was December and June (1). The highest prevalence (40 %) was observed in winter and the lowest (10 %) was in the rainy season. The maximum prevalence (50 %) was recorded in male fish in summer and autumn. However, the mean intensity (6.5), index of infection (3.71), and abundance (1.85) were highest in female fishes. The prevalence (30.23 %), abundance (0.74), and index of infection (0.68) were observed maximum in smaller size group and the lowest in large size group (24.44 %, 0.38 %, and 4.16 respectively). There was a variation of infestation of fish according to length, sex, season, and sources. Vol. 10, No. 3, December 2023: 367-376